Imaging the uptake of deuterated methionine in Drosophila with stimulated Raman scattering - Spratt, Spencer J.; Mizuguchi, Takaha; Akaboshi, Hikaru; Kosakamoto, Hina; Okada, Rina; Obata, Fumiaki; Ozeki, Yasuyuki (Frontiers in Chemistry, 2023)
Introduction: Visualizing small individual biomolecules at subcellular resolution in live cells and tissues can provide valuable insights into metabolic activity in heterogeneous cells, but is challenging. Methods: Here, we used stimulated Raman scattering (SRS) microscopy to image deuterated methionine (d-Met) incorporated into Drosophila tissues in vivo. Results: Our results demonstrate that SRS can detect a range of previously uncharacterized cell-to-cell differences in d-Met distribution within a tissue at the subcellular level. Discussion: These results demonstrate the potential of SRS microscopy for metabolic imaging of less abundant but important amino acids such as methionine in tissue.